2016
DOI: 10.1002/pbc.26105
|View full text |Cite
|
Sign up to set email alerts
|

Relapsed/refractory pediatric B‐cell non‐Hodgkin lymphoma treated with rituximab combination therapy: A report from the Japanese Pediatric Leukemia/Lymphoma Study Group

Abstract: The prognosis of pediatric R/R B-NHL in a Japanese cohort remained poor but is showing improvement in the rituximab era. Rituximab combination therapy is effective for R/R B-NHL patients who did not receive rituximab as primary treatment. We need to consider possible viral infections in allogeneic HSCT after rituximab treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
2
14
2
1
Order By: Relevance
“…The number of patients with large B-cell lymphoma was too small to properly address the impact of rituximab in this population, but, by contrast to BL, rituximab appears to improve large B-cell lymphoma outcome at relapse in this series as in other pediatric reports. 12,19,22 In a recent study, Osumi et al 23 The ORR to salvage chemotherapy was 65% in our cohort, with 47% in CR. The number of patients per type of salvage chemotherapy group was small, but as previously reported, 2,8 R-CYVE seemed to be effective in patients previously treated in group B (without high-dose cytarabine or etoposide) with an ORR of 72% (56% CR).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The number of patients with large B-cell lymphoma was too small to properly address the impact of rituximab in this population, but, by contrast to BL, rituximab appears to improve large B-cell lymphoma outcome at relapse in this series as in other pediatric reports. 12,19,22 In a recent study, Osumi et al 23 The ORR to salvage chemotherapy was 65% in our cohort, with 47% in CR. The number of patients per type of salvage chemotherapy group was small, but as previously reported, 2,8 R-CYVE seemed to be effective in patients previously treated in group B (without high-dose cytarabine or etoposide) with an ORR of 72% (56% CR).…”
Section: Discussionsupporting
confidence: 52%
“…In a recent study, Osumi et al reported the outcome of 33 pediatric Japanese patients with refractory or relapsed mature B‐NHL treated with second‐line therapy including rituximab. Although our two cohorts had the same number of patients, our results differ, as the Japanese study showed better outcome and a benefit in using rituximab, with a 5‐year overall survival rate of 48.5%.…”
Section: Discussionmentioning
confidence: 80%
“…Upon 980 nm excitation, the MCL cell surface would emit bright double-colour upconversion fluorescence. In addition, the anti-CD20 monoclonal antibody known as rituximab is a chemo-therapeutic drug, which has been widely used in the treatment of NHL derived from B-cells [ 43 45 ]. The anti-tumour mechanism of rituximab is mainly dependent on antibody-dependent cell cytotoxicity (ADCC) and complement-dependent cytotoxicity (CDC) [ 46 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, prognostic factors have been extensively analyzed. However, the results are not always consistent and it is difficult to compare the analyses of studies that differ in terms of patients’ selection (refractory and relapsed or only relapsed), histologic subtype (BL alone or all the histologic B‐NHL, including also PMBCL) and salvage regimens (Anoop et al , 2012; Kim et al , 2014; Jourdain et al , 2015; Osumi et al , 2016; Cairo et al , 2018; Rigaud et al , 2019). Several prognostic factors have been analyzed, including the initial characteristics and treatment of the disease, the histologic subtype, the time and type of failure, the response to salvage treatment and, finally, the possibility or not of carrying out an HSCT.…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…As already discussed, there is limited information on salvage regimens for paediatric r/r B‐NHL with data on small series of patients, heterogeneous for histology, disease status and patient selection. The efficacy of a single salvage regimen in eligible patients (Gentet et al , 1990; Kobrinsky et al , 2001; Griffin et al , 2009; Osumi et al , 2016) or the survival in a population of r/r patients treated with different regimens has been evaluated from different points of view (Jourdain et al , 2015; Rigaud et al , 2019). Table III describes results from published studies.…”
Section: Salvage Regimensmentioning
confidence: 99%